F-BAR Proteins of the Syndapin Family Shape the Plasma Membrane and Are Crucial for Neuromorphogenesis - Dharmalingam, Elavarasi (J Neurosci, 2009)
Coordinated functions of the actin cytoskeleton and microtubules, which require careful control in time and space, are indispensable for the drastic alterations of neuronal morphology during neuromorphogenesis and neuronal network formation. Actin filament formation driven by the Arp2/3 complex and its activator neural Wiskott-Aldrich syndrome protein (N-WASP) is important for proper axon development. The underlying molecular mechanisms for targeting to and specific activation of N-WASP at the neuronal plasma membrane, however, have thus far remained elusive. We show that syndapin I is critical for proper neuromorphogenesis and hereby uses N-WASP as a cytoskeletal effector. Upon N-WASP binding, syndapins release N-WASP autoinhibition. Syndapins hereby cooperate with Cdc42 and phosphatidyl-inositol-(4,5)-bisphosphate. Syndapins furthermore specifically bind to phosphatidylserine-containing membranes via their extended F-BAR domain. Dissecting the syndapin functions actin nucleation and direct membrane binding in vivo, we demonstrate that both functions are physiologically relevant and required. Constitutive plasma membrane-targeting experiments in vivo indicate that specifically actin nucleation at the cell cortex is triggered by syndapins. Consistent with syndapins steering N-WASP as downstream effector for cortical actin nucleation, syndapin-induced neuronal arborization is N-WASP and Cdc42 dependent. The functions of syndapin–N-WASP complexes in neuromorphogenesis were revealed by loss-of-function studies. Knockdown of syndapin I leads to impaired axon development and especially phenocopies the aberrant axon branching observed upon N-WASP and Arp2/3 complex deficiency. In contrast, proper length control involves another N-WASP-binding protein, Abp1. Our data thus reveal that syndapin I is crucial for neuromorphogenesis and that different N-WASP activators ensure fine control of N-WASP activity and have distinct functions during neuronal network formation.